Treatment Protocols - Dr. Devendra Prasad K J; Praveen, Dr.; Dixit, Dr. Manasa (Story of Sepsis, Edition 1, 2025)
The 2021 Surviving Sepsis Campaign Guidelines delineate evidence-based protocols for the management of adult sepsis and septic shock, underscoring the importance of swift identification and intervention, in conjunction with holistic care methodologies. The enduring incidence of sepsis underscores the imperative for ongoing research and educational initiatives within this domain. The facilitation of early diagnosis is supported by screening instruments such as SIRS, SOFA, and qSOFA, along with laboratory evaluations including lactate and C-reactive protein concentrations. Innovative utilization of machine learning and artificial intelligence are presently being explored for screening applications; nevertheless, they require further empirical validation. Early fluid resuscitation holds critical importance; yet, the ideal volume remains contentious, with the once-accepted guideline of 30 ml/kg being redefined as merely a suggestion. While conventional metrics such as Central Venous Pressure (CVP) and Pulmonary Capillary Wedge Pressure (PCWP) inform fluid therapy, they exhibit considerable limitations, thereby necessitating a comprehensive clinical assessment. Dynamic evaluations, including Passive Leg Raising (PLR) and Inferior Vena Cava (IVC) indices, improve the assessment of fluid responsiveness, albeit with varying degrees of precision. The 2021 Guidelines recommend the use of crystalloids as the primary fluids, identify norepinephrine as the vasopressor of choice, and prescribe targeted ventilation strategies for the management of respiratory failure and Acute Respiratory Distress Syndrome (ARDS).